The Implications of Ajengan Ruhiat's Thought and Contributions in the Network of Intellectual Scholars in West Java - Yuda S, Dendi (UIN Sunan Gunung Djati Bandung, 2023)
This research endeavors to scrutinize the persona, ideologies, and pivotal role of KH. Ruhiat in shaping the intellectual ulama network within the West Java region. Furthermore, it delves into the intricate nexus with the Cipasung Islamic Boarding School, situated in Tasikmalaya, which was founded by KH. Ruhiat. This institution has endured over time, generating a cadre of ulama figures who have made substantial contributions to the dissemination and expansion of KH. Ruhiat’s intellectual legacy. Employing a historical and qualitative framework, this study undertakes the comprehensive exploration of the profound influence and presence of ulama figures, most notably KH. Ruhiat, in the establishment of the ulama network within West Java. Methodologically, the research adopts a case study approach, focusing on the profiling of a prominent ulama figure in West Java. Data collection methods encompass meticulous documentation, astute observation, and in-depth interviews. The findings of this investigation underscore the pivotal role played by KH. Ruhiat in the resistance against Dutch colonialism and in catalyzing nationalistic consciousness among the populace. His endeavors in education and religious advocacy effectively galvanized the community towards the pursuit of Indonesian independence. Notably, KH. Ruhiat assumed a pivotal position in the formation of the ulama-intellectual network in West Java, particularly at the Cipasung Islamic Boarding School. This network was meticulously constructed through genealogical lines of descent, marriage alliances, and scholarly transmission. The architectural framework of the core and satellite boarding schools emerged as instrumental components in the establishment of this extensive network. Furthermore, matrimonial unions among the progeny of ulama, accomplished senior santri, and individuals possessing scholarly acumen emerged as efficacious mechanisms for the consolidation of the ulama-intellectual network